ANNE CONWAY'S PHILOSOPHY OF RELIGION. Issue 59 (2021) - Burns, Elizabeth
Abstract : Anne Conway (1631–79) produced only one short treatise – The Principles of the Most Ancient and Modern Philosophy – but addressed key problems in the philosophy of religion which are still much discussed today. The most significant of these are the problem of religious diversity and the problem of evil. Although the sources of her ideas may be found in the Kabbalah of Isaac Luria and the work of the Cambridge Platonists and the Quaker George Keith, among others, she offers her own unorthodox solutions to these problems. The idea of Christ as an indwelling mediator of the divine who assists us in our moral endeavours is designed to appeal to those of all religions and none, while her claim that God created creatures knowing that they would eventually be redeemed, and that suffering promotes moral development which leads to redemption offers a novel response to the problem of evil. Conway's work is also important for its influence on the work of Gottfried Wilhelm Leibniz, and some have argued that it prefigures, at least in outline, the field theory of modern physics.